2011
DOI: 10.3171/2011.3.jns101333
|View full text |Cite
|
Sign up to set email alerts
|

Awake surgery for WHO Grade II gliomas within “noneloquent” areas in the left dominant hemisphere: toward a “supratotal” resection

Abstract: These findings support the usefulness of awake surgery with intraoperative functional (language) mapping with the attempt to perform supratotal resection of LGGs involving noneloquent areas in the left hemisphere. Indeed, the extent of resection was significantly increased in all cases but 2, with no additional permanent deficit and with control of seizures in all patients. The goal of supracomplete resection is currently to delay the anaplastic transformation, even if it does not (yet) enable a cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
209
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(220 citation statements)
references
References 38 publications
3
209
0
8
Order By: Relevance
“…2,29,49,50,53 Indeed, despite the lack of Class I evidence demonstrating that DLGG surgery improved survival, Jakola et al 29 recently investigated survival in population-based parallel cohorts of patients with DLGGs from 2 Norwegian university hospitals with different surgical treatment strategies. They demonstrated that treatment at a center that favored early resection was associated with better overall survival (median survival not reached) than treat- Object.…”
mentioning
confidence: 99%
“…2,29,49,50,53 Indeed, despite the lack of Class I evidence demonstrating that DLGG surgery improved survival, Jakola et al 29 recently investigated survival in population-based parallel cohorts of patients with DLGGs from 2 Norwegian university hospitals with different surgical treatment strategies. They demonstrated that treatment at a center that favored early resection was associated with better overall survival (median survival not reached) than treat- Object.…”
mentioning
confidence: 99%
“…DES plays an important role in studies of such higher cognitive functions as hemispheric ignorance, perceptual awareness, music, calculation, memory and category-specific naming (12,(34)(35)(36)(37)(38)(39). In the present study, it was found that the Broca area of a Chinese population undergoing DES was mainly concentrated within a 1-cm range.…”
Section: Discussionmentioning
confidence: 55%
“…As a consequence, as recommended by the European guidelines, early surgery is currently the first treatment option to consider in DLGG [24]. This is the reason why some authors have achieved "supratotal" resection (i.e., extended resection with a margin beyond MR imaging-defined abnormalities) [25], especially in asymptomatic patients with incidental discovery of DLGG [8,18]. Thanks to the use of intraoperative functional mapping at both the cortical and subcortical level, favorable oncological and functional outcomes have been obtained [6].…”
mentioning
confidence: 99%
“…Indeed, it could be ethically acceptable to propose to a patient to voluntarily generate a permanent neurological deficit if it were possible to cure him or her. Nonetheless, even in cases of supratotal resection for DLGG located outside eloquent areas, whereas no malignant transformation has been observed yet, tumor relapse has already occurred [25]. Therefore, why elicit disabling sequelae by maximizing the resection for DLGG involving functional structures, knowing that the glioma will inescapably recur?…”
mentioning
confidence: 99%